1970
DOI: 10.3329/bjb.v39i2.7301
|View full text |Cite
|
Sign up to set email alerts
|

Limnology of Lake Bogakain, Bandarban, Bangladesh

Abstract: Bogakain, a natural high altitude (372 m) lake of Bangladesh has been limnologically investigated for the first time. At mid-point, the depth of the lake was measured 46.54 m and the Secchi visibility was 2.37 m. Water temperature from 1-10 m depth gradient showed slight stratification in the lake which varied from 27.0 - 22.4° C at 1.00 pm. pH at the different depths ranged from 7.8 - 9.1, conductivity from 75 - 80 μS/cm and TDS from 39 - 42 mg/l. Alkalinity ranged from 0.8 - 1.24 meq/l and DO from 0.61 - 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…TDS, conductivity, alkalinity and NO 3 -N were higher than Bogakain while water temperature, pH and DO were closer in both the lakes. The high value of PO 4 -P was observed in lake Bogakain (Khondker et al 2010) compared to Lake Ashura. In lake Bogakain, the total density of phytoplankton varied from 686.62×10 3 -409381.73×10 3 ind/l (Khondker et al 2010).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…TDS, conductivity, alkalinity and NO 3 -N were higher than Bogakain while water temperature, pH and DO were closer in both the lakes. The high value of PO 4 -P was observed in lake Bogakain (Khondker et al 2010) compared to Lake Ashura. In lake Bogakain, the total density of phytoplankton varied from 686.62×10 3 -409381.73×10 3 ind/l (Khondker et al 2010).…”
Section: Resultsmentioning
confidence: 83%
“…The proportion (%) of recorded species of Cyanophyceae, Chlorophyceae and Cryptophyceae was lower in Lake Ashura than Lake Bogakain (Khondker et al 2010). Recorded species of Euglenophyceae in Bogakain is lower where diversity is highest in Lake Ashura.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Highest value of dissolved oxygen (9.90 mg/l) in Ramsagar lake was recorded in the month of February and the lowest value (5.10 mg/l) in the month of May. Khondker et al (2010) found DO concentration varied between 0.61 to 11.39 mg/l at lake Bogakain, Bandarban, Bangladesh. It might be due to alteration of photosynthesis, abundance of phytoplankton, respiration by fish and other aquatic organisms of the lake.…”
Section: Physico-chemical Parametersmentioning
confidence: 99%